Advancing Institutional Engagement for Sustainable Livestock Production in Pampas Region of Argentina: Challenges and Opportunities - Recavarren, Paulo Mario; Caldentey, Francisco; Faverin, Claudia (International Livestock Research Institute (ILRI) y Norwegian Institute of Bioeconomy Research (NIBIO)., 2025)
Poster